Green Microfinance and Women’s Empowerment: Mediating Role of Financial Literacy - Sedhai, Prashanna; Balami, Surya; Pandey, Nabin (Journal of Innovation in Academia, 2025)
This study examines the influence of green microfinance (GMF) on women's empowerment (WE) through the mediating role of financial literacy (FL), integrating human capital theory, capability approach, and experiential learning theory. Based on a survey research design, data were purposively collected from 250 women affiliated with three leading microfinance institutions (MFIs), each having at least a minimum participation period of six months. Data were analyzed using Structural Equation Modeling. The findings revealed that GMF significantly influenced FL but did not have a significant effect on WE. Moreover, the relationship between FL and WE was supported, and the mediating role of FL in this relationship was also confirmed. This indicates that GMF fosters empowerment primarily by enhancing women’s financial knowledge and decision-making abilities. The study extends microfinance and feminist empowerment theories by introducing the environmental dimension of GMF and positioning FL as a key mediating factor.